(untitled) (Eurasian Journal of Engineering and Technology, 2026)
This article examines the reliability of scientific research results on improving the energy characteristics and efficiency of a stand-alone inverter. The study also analyzes the correlation between the reliability of these results and variations in the inverter’s input voltage range.